Utilizando o GeoGebra para compreensão as relações métricas no triângulo retângulo - Bispo, Sérgio Otavio (2023)
The use of digital technologies has become increasingly necessary in classrooms. One of the areas that have benefited most from these technologies is Mathematics. Software and applications, such as GeoGebra, show good results when used by the teacher in explaining mathematical content, especially in relation to geometry. This work presents a sequence of activities over five classes with an 8thgrade elementary school class. The purpose of these activities was to present the metric relationships in a right triangle. For this, the concepts of congruence and similarity of figures, especially triangles, were examined. In these activities, carried out in the computer lab, the teacher used GeoGebra to explain the contents and examples while the students solved exercises, also using GeoGebra on their computers. As reported in the text, the student’s interaction with the teacher shows that the activities aroused the students’ interest in learning. In addition, with the evaluation of the test applied in the last class, we can conclude that the use of GeoGebra contributed to learning in the teaching of relations in the triangle.